Democratic Recession and Illiberal Peacbuilding in Latin America: A Case Study of the Guyana- Venezuela Conflict - Putri Callista Sadhya; Adhi Cahya Fahadayna; Reza Triarda (PT ARRUS Intelektual Indonesia, 2026)
This article explores the intersection of the processes and dynamics of democratic regression, illiberal peacebuilding and path dependence in the?context of the Guyana-Venezuela territorial dispute for the Essequibo region. It was based on colonial era resentment, and has been worsened by the oil discovery - it speaks?to different but equally implacable forms of conflict resolution. Venezuela uses nationalist mobilization and autocratic means for domestic hegemony, while its partner Guyana resorts to technocratic legalism?in the form of international adjudication, all too often avoiding broad-based public participation. The analysis employs a qualitative comparative-historical analysis (CHA) within an HI approach to demonstrate how path?dependent institutional behavior influences state response to geopolitical disputes. The study makes comparisons to other international disputes, including Russia's forcible annexation of Crimea and China's construction works?in the South China Sea, with a view to illustrating how territorial conflicts can be exploited by illiberal regimes. The evidence indicates that procedural?democracy without participation and overt authoritarianism support the erosion of democratic governance. The article argues in favour of transparent, inclusive and?participatory peace-building approaches with regional organizations and impartial mediators. It maintains?that a sustainable solution to conflict must harmonize legal structures and democratic values when dealing with territorial disputes and domestic challenges to regime legitimacy in the Latin American context.